Visit of President Dr. A.P.J. Abdul Kalam to Singapore, Philippines, and Republic of Korea, 1 to 8 February, 2006. - Abdul Kalam, A. P. J. (Avul Pakir Jainulabdeen) 1931-2015 (External Publicity Division, Ministry of External Affairs, 2006)
Selected speeches of the President of India during his visits to the Singapur, Philippines, and Republic of Korea in Feb. 2006.